2010
DOI: 10.1371/journal.pone.0015583
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK and JNK Antagonistically Control Senescence and Cytoplasmic p16INK4A Expression in Doxorubicin-Treated Endothelial Progenitor Cells

Abstract: Patients treated with low-dose anthracyclines often show late onset cardiotoxicity. Recent studies suggest that this form of cardiotoxicity is the result of a progenitor cell disease. In this study we demonstrate that Cord Blood Endothelial Progenitor Cells (EPCs) exposed to low, sub-apoptotic doses of doxorubicin show a senescence phenotype characterized by increased SA-b-gal activity, decreased TRF2 and chromosomal abnormalities, enlarged cell shape, and disarrangement of F-actin stress fibers accompanied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
71
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 48 publications
8
71
0
Order By: Relevance
“…Although nuclear expression of CDKN2A is usually associated to cell-cycle control, cytoplasmic accumulation has also been associated to senescent phenotype induced by stress. 68 Histological studies suggest that non-ciliated secretory cells give rise to ciliated cells and function as a long-term self-renewing stem cell population in the intrapulmonary airways. 59 In addition, it has been reported that the adult mouse lung contains a minor population of multipotent epithelial stem cells with the capacity of self-renewal and to give rise to all epithelial progenitors that reside in discrete microenviromental niches along the proximal-distal axis.…”
Section: Discussionmentioning
confidence: 99%
“…Although nuclear expression of CDKN2A is usually associated to cell-cycle control, cytoplasmic accumulation has also been associated to senescent phenotype induced by stress. 68 Histological studies suggest that non-ciliated secretory cells give rise to ciliated cells and function as a long-term self-renewing stem cell population in the intrapulmonary airways. 59 In addition, it has been reported that the adult mouse lung contains a minor population of multipotent epithelial stem cells with the capacity of self-renewal and to give rise to all epithelial progenitors that reside in discrete microenviromental niches along the proximal-distal axis.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that SIPS rather than apoptosis is a predominant response of human adult cells challenged with various stressors: hydrogen peroxide (Orciani et al 2010;Brandl et al 2011a, b), ionizing radiation (Suzuki and Boothman 2008), gamma radiation (Cmielova et al 2012), doxorubicin (Spallarossa et al 2010), and tumor necrosis factor alpha (Zhang et al 2009). It was generally accepted that SIPS is an important tumor suppression mechanism preventing the proliferation of cells that are at risk of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it has been shown that p38MAPK inhibition can maintain hematopoietic stem cell quiescence, inhibiting the exhaustion of the hematopoietic stem cell pool (Ito, et al, 2006). In addition, p38MAPK inhibition can reduce cellular senescence in EPC exposed to doxorubicin (Spallarossa, et al, 2010). No data are available regarding hCSC.…”
Section: Drug-based Strategy To Enrich In Non-senescent Cellsmentioning
confidence: 99%